Clustered regulatory interspaced short palindromic repeats (CRISPR)-mediated mutagenesis and phenotype rescue by piggyBac transgenesis in a nonmodel Drosophila species - Tanaka, R.; Murakami, H.; Ote, M.; Yamamoto, D. (Insect molecular biology, 2016)
How behavioural diversity emerged in evolution is an unexplored subject in biology. To tackle this problem, genes and circuits for a behaviour need to be determined in different species for phylogenetic comparisons. The recently developed clustered regulatory interspaced short palindromic repeats/CRISPR associated protein9 (CRISPR/Cas9) system made such a challenge possible by providing the means to induce mutations in a gene of interest in any organism. Aiming at elucidating diversification in genetic and neural networks for courtship behaviour, we attempted to generate a genetic tool kit in Drosophila subobscura, a nonmodel species distantly related to the genetic model Drosophila melanogaster. Here we report the generation of yellow (y) and white mutations with the aid of the CRISPR/Cas9 system, and the rescue of the y mutant phenotype by germline transformation of the newly established y mutant fly line with a y+‐marked piggyBac vector. This successful mutagenesis and transformation in D. subobscura open up an avenue for comprehensive genetic analyses of higher functions in this and other nonmodel Drosophila species, representing a key step toward systematic comparisons of genes and circuitries underlying behaviour amongst species.